Modeling the Mechanisms and Outcomes of Credit and Financial Shocks Using a Dynamic Stochastic General Equilibrium (DSGE) Model - Ranjbari , Mohammad; Izadi, Hossein; Jahangirnia , Hossein; Zanjerdar, Majid (Management Strategies and Engineering Sciences, 2025)
In the Iranian economy, changes in bank deposit interest rates—as tools for implementing credit and monetary policies—have become a major concern for policymakers and macroeconomic authorities, due to the various channels and mechanisms through which they affect the economy and contribute to economic fluctuations. An examination of the Central Bank’s monetary and credit policies and the trend of bank deposit interest rates over the past two decades affirms this concern. Monetary authorities, in response to inflationary changes on the one hand, and the need to finance the production sector on the other, have consistently been compelled to alter deposit interest rates. Simultaneously, the financial asset market has repeatedly experienced conditions of recession, expansion, and severe volatility. Therefore, it appears crucial that, in order to design and implement effective credit policies for Iran’s economy, a thorough investigation into the impacts of both stochastic and non-stochastic credit and financial shocks on key macroeconomic variables be conducted. Such policies should account for the mechanisms through which these shocks are transmitted to the economy and consider the implications of changes in deposit interest rates and lending rates. Particularly within the framework of models based on microeconomic theoretical foundations, the absence of a comprehensive and cohesive domestic body of literature on this topic underscores its significance even further. Previous studies indicate that incorporating the banking sector within DSGE models enhances the explanatory and fitting power of the models, aligning simulation results more closely with the actual behavior of macroeconomic variables in Iran. Prior research also reveals that financial frictions, financial and credit volatility, and changes in bank interest rates significantly affect the behavior of variables within the real economy. Consequently, the banking sector plays a critical role in triggering and amplifying macroeconomic fluctuations. The findings suggest that, in the event of both technology and oil revenue shocks, an inflation-targeting policy scenario induces less volatility in output and employment levels compared to an exchange rate-targeting scenario.